Edukasi Penggunaan Hand Sanitizer Dan Cairan Desinfektan Untuk Pencegahan Penyebaran Covid-19 Di Wilayah Desa Talia Kecamatan Abeli Kota Kendari: Education on the Use of Hand Sanitizers and Disinfectants to Prevent the Spread of Covid-19 in the Talia Village, Abeli District, Kendari City - Wa Ode Yuliastri; La Ode Muhammad Andi Zulbayu; Muhammad Isrul; Silviana Hasanuddin; Nikeherpianti Lolok (Jurnal Mandala Pengabdian Masyarakat, 2020)
The spread of Covid-19 in Indonesia still became the main concern for the Central Government, Regional Government and the community. The unavailability of drugs or vaccines in terms of preventing and treating Covid-19 infection has had a major impact on the social and economy of the community. One of the highlights is the availability of hand sanitizers and disinfectants which are very rare and the prices are very high, especially in Kendari City. One of the areas for education related to the production and use of hand sanitizers and disinfectants is Talia Village, Abeli ??District, Kendari City. The purpose of this activity is to educate the people of Talia Village about the use of hand sanitizers and disinfectants to prevent the spread of Covid-19. The method of implementing this service activity is carried out by making an educational video on how to make and use the correct and right target hand sanitizer and disinfectant preparations. The result of this activity is an increased understanding of the community about the manufacture and use of hand sanitizers and disinfectants. This is based on people who are active and enthusiastic in asking questions to find out how to prevent the spread of the Covid-19 virus.